The Effect of Group Investigation Learning Model Assisted by Movie Media on the Ability to Identify the Elements of Drama on Identify Elements of Drama in Students of Class VIII SMP Istiqlal Delitua Learning Year 2022/2023 - Hasanah, Nurul; Febriyana, Mutia (Proceeding International Conference on Malay Identity, 2023)
This research aims to determine the effect of the Group Investigation learning model assisted by film media on the ability to identify drama elements in class VIII Istiqlal Delitua Middle School students in the 2022/2023 academic year. This type of research method is quantitative with an experimental type. This research uses a post-test only control design type. The population in this study was all 4 classes of VIII class totaling 110. The research sample consisted of 2 classes, namely class VIII-2 as the experimental class and class VIII-3 as the control class using random sampling techniques. The instrument used is an essay test which contains 1 question, namely analyzing the elements of drama. The results of this research show that the ability to identify drama elements in class VIII Istiqlal Delitua Middle School students in the 2022/2023 academic year using the Group Investigation model assisted by film media is in the good, very good category because they obtained an average of 81.64, while the ability to identify elements The drama element with the Problem Based Learning model is in the poor category because it obtained an average of 69.96. Based on the results of the test carried out, namely by comparing tcount with ttable, it was obtained that tcount > ttable, namely 2.755 > 2.0048, it can be concluded that there is an influence of the Group Investigation learning model assisted by film media on the ability to identify drama elements in class VIII SMP students. Istiqlal Delitua for the 2022/2023 academic year.